National Accounts Studies of the ESCWA Region, Bulletin No. 27 - United Nations Economic; Social Commission for Western Asia (United Nations, 2007)
This publication provides national statistics on the countries of Western Asia. The data includes aggregates of national accounts and their relative distribution, consolidated national accounts for each country during the period 2002-2006, and estimates of gross domestic product. This publication is both in English and Arabic.